Speed Reading Skills by Using Skimming Techniques In Digital Newspaper Articles - Rizka Rahayu; Prana Dwija Iswara; Tatat Hartati; Babang Robandi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
The purpose of this study is to analyse student’s speed reading skill after participating the learning of reading by Skimming technique of digital newspaper at 5th grade in Elementary School. This study was practiced at one of Elementary School in Kecamatan Sumber, Kabupaten Cirebon. The subject of this activity is 25 students of 5th grade. This study used Action Research Method. Based on the results of the analysis, there was an increase in the aspect of student test scores in the pre-research with a score of 70 by 40%, at the end of the first cycle a score of 60% was obtained, and at the end of the second cycle the score increased to 84%. The results of speed reading skills in cycle II have exceeded the specified target. Based on the results of observations made, data were obtained that showed success in improving speed reading skills and increasing student’s understanding in the learning process using the Skimming technique. Thus, it can be concluded that the Skimming technique is able to improve the speed reading skills of 5th grade students in one of the public elementary schools in Kecamatan Sumber, especially in the text contained in digital newspapers, in addition to increasing speed reading skills, there is also a better change in the attitudes of participants students as a form of habituation of discipline in speed reading activities and implemented in other activities in the learning process.